Sthiti and Yatna in the Abhyāsa of Yoga: A Textual Study Based on 15 Saṃskṛta Commentaries of Yogasūtra - Jayaraman Mahadevan (Wolters Kluwer Medknow Publications, 2021)
Background: Awareness about Yoga as a system of healing has increased in the current era. Various limbs of Yoga with their therapeutic benefits are being practiced and their efficacy is being investigated. But Yoga is not a onetime pill. It has to be practiced in a sustained and beneficial manner over a period of time for its benefits to manifest. Aim and Objectives: In Yogic parlance Abhyāsa is the term generally used to indicate practice. Yogasūtra, the fundamental text on Yoga defines Abhyāsa. In this context a comprehensive review of Yogasūtra Saṃskṛta commentary literature with specific focus on the definition of Abhyāsa is essential, which has hitherto not been attempted. Material and Methods: Fifteen Saṃskṛta commentaries have been surveyed and analysed for the current paper with focus on the definition of abhyāsa found in the sūtra - tatra sthitau yatno'bhyāsaḥ PYS 1.13. Result: The analysis of the Saṃskṛta commentary literature on this offers clarifications on the two sthiti-s of Yoga that is to be attained through the Yatna that has five dimensions. Conclusion: Though the inputs from the commentary lore discuss Abhyāsa in the spiritual, philosophical context- the implications of Abhyāsa in the therapeutic dimensions of Yoga are immensely useful. The outcomes of this textual review on being imbibed and incorporated in the practice of Yoga may add to the quality of Yoga practice there by facilitating better outcomes in Yoga aimed at health and wellbeing.